Land Use Planning in Western Uttar Pradesh: Issues and Challenges - and Zubairul Islam2, R. P. Singh1 (Recent Research in Science and Technology, 2010)
Abstract Western Uttar Pradesh is a part of gangetic plain. Agriculture is the prime occupation of the people here. Population of the region has grown up because of easy availability of fertile land and water. Unplanned development of agriculture has produced critical issues such as decreasing size of agricultural land holding, soil degradation and lowering of underground water level.